2014
DOI: 10.2147/ijn.s57314
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of psoralen ethosomes for topical delivery in rats by using in vivo microdialysis

Abstract: This study aimed to improve skin permeation and deposition of psoralen by using ethosomes and to investigate real-time drug release in the deep skin in rats. We used a uniform design method to evaluate the effects of different ethosome formulations on entrapment efficiency and drug skin deposition. Using in vitro and in vivo methods, we investigated skin penetration and release from psoralen-loaded ethosomes in comparison with an ethanol tincture. In in vitro studies, the use of ethosomes was associated with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(27 citation statements)
references
References 34 publications
1
26
0
Order By: Relevance
“…14 Ethosomes are a novel type of liposomes containing a high concentration of shortchain alcohols, including ethanol, propylene glycol, or even a mixture of ethanol and propylene glycol. [15][16][17] The addition of ethanol improves the deformability of vesicles, thus overcoming some of the disadvantages of the conventional liposomes, but also carries the risk of skin irritation.…”
Section: Introductionmentioning
confidence: 99%
“…14 Ethosomes are a novel type of liposomes containing a high concentration of shortchain alcohols, including ethanol, propylene glycol, or even a mixture of ethanol and propylene glycol. [15][16][17] The addition of ethanol improves the deformability of vesicles, thus overcoming some of the disadvantages of the conventional liposomes, but also carries the risk of skin irritation.…”
Section: Introductionmentioning
confidence: 99%
“…The in vitro RL was 35 ± 2 %, and it was similar to the RR in vitro, which indicated that PAB transport across probe membrane from the perfusate into the surrounding tissue was equal to that from the tissue into the perfusate. Therefore, the in vivo RL by retrodialysis was taken as the in vivo RR (Zhang et al, 2014). The in vivo RL was 34 ± 1 %, and it was also independent of the perfusate concentration, validating that the in vivo RR could be used to calibrate the PAB concentration in the skin.…”
Section: Dermal Pharmacokinetics Studiesmentioning
confidence: 91%
“…In vivo skin microdialysis study showed that the peak concentration and area under the curve of psoralen from ethosomes were approximately 3 and 2 times higher than those of psoralen from the tincture formulation indicating potential of ethosomal psoralen for improved treatment of vitiligo [92].…”
Section: Deformable (Elastic) Liposomesmentioning
confidence: 98%